Efecto de la hidroxipropil metilcelulosa en la velocidad de disolución de tabletas de diclofenaco sódico - Díaz Buenaño, Guiselle Carmen (2007)
The present investigation work was guided to determine the effect of the Hydroxypropyl methylcellulose (HPMC) about the speed of dissolution of Diclofenac sodium tablets. Eight formulations were essayed according to a factorial design of three factors: HPMC, Cellulose microcrystalline (CMC) and Lactose, whit two levels each one (high and lower). For the dissolution essay were used 12 tablets for each formulation, beginning with half gastric artificial without enzyme (pH 1.2) using the apparatus 2 of the USP XXVIII, to 100 rpm and a temperature of 37 ± 0.5 °C. This one worked for a period of 480 minutes. With the obtained data, it was determined the dissolution parameters starting from the dissolved quantities of Diclofenac sodium versus time, it adjusted to the model of order zero. The interval of the dissolution constants was between 0.1546 and 0.2037 Kd mg/min, not existing a significant difference among them